Reactive oxidized nitrogen speciation and partitioning in urban and rural New York State. (4th March 2021) - Ninneman, Matthew; Marto, Joseph; Shaw, Stephanie; Edgerton, Eric; Blanchard, Charles; Schwab, James
ABSTRACT: This study examined reactive oxidized nitrogen (NOy ) speciation and partitioning at one urban site, Queens College (QC) in New York City, and one rural site, Pinnacle State Park (PSP) in Addison, New York (NY) from September 2016 to August 2018 and June 2016 to September 2018, respectively. Oxides of nitrogen (NOx ), nitric acid (HNO3 ), particle nitrate (pNO3 ), peroxy nitrates (PNs), alkyl nitrates (ANs), and NOy measurements were made at both sites. Across all seasons at QC, the median NOx, HNO3, pNO3, PNs, ANs, and NOy concentrations were 10.99, 0.49, 0.24, 0.62, 0.94, and 13.95 parts per billion (ppb), respectively. All-season median percent contributions of NOx, HNO3, pNO3, PNs, and ANs to the total NOy at QC were 77, 4, 2, 5, and 7%, respectively. Therefore, the sum of the individual NOy species (NOyi ≈ NOx + HNO3 + pNO3 + PNs + ANs) accounted for 95% of the total NOy at QC, which was well within measurement uncertainties. At PSP, the median NOx, HNO3, pNO3, PNs, ANs, and NOy concentrations were 0.65, 0.16, 0.12, 0.13, 0.18, and 1.56 ppb, respectively, over all seasons. The median percent contributions of NOx, HNO3, pNO3, PNs, and ANs to NOy over all seasons at PSP were 42, 10, 8, 9, and 12%, respectively. NOyi comprised 81% of NOy across all seasons at PSP, and deviations from 100% closure were generally within measurement uncertainties. Since both datasets yielded NOy budget closure results that were either fully or largely explained by the measurement uncertainties, the observed NOyi is likely representative of ambient NOy in urban and rural New York. The results have implications for understanding the fate of NOx emissions and their impact on local and regional air quality in urban and rural New York State. Implications : Continuous speciated and total reactive oxidized nitrogen (NOy ) measurements were made in urban and rural New York from 2016 to 2018. Different NOy species have contrasting effects on the chemistry that impacts ozone (O3 ) and fine particulate matter (PM2.5 ) formation and concentrations. Since O3 and PM2.5 are regulated pollutants that have proven difficult to control, the results have implications for current and future air quality policy.